Propionic acid supplementation promotes the expansion of regulatory T cells in patients with end-stage renal disease but not in renal transplant patients - Anft, Moritz; Meyer, Fabian; Czygan, Sirin; Seibert, Felix S.; Rohn, Benjamin J.; Tsimas, Fotios; Viebahn, Richard; Westhoff, Timm H.; Stervbo, Ulrik; Babel, Nina; Zgoura, Panagiota (Frontiers in Transplantation, 2024)
In a previous study, we showed an anti-inflammatory effect of propionic acid supplementation in dialysis patients. The present study intends to analyze the effect of propionic acid on the chronic inflammatory state and T-cell composition in kidney transplant patients compared to dialysis patients. A total of 10 dialysis patients and 16 kidney transplant patients under immunosuppressive standard triple immunosuppressive therapy received 2 × 500 mg propionic acid per day for 30 days. The cellular immune system was analyzed before and after the propionic acid supplementation and 30–90 days thereafter as a follow-up. We measured the main immune cell types and performed an in-depth characterization of T cells including regulatory T cells (Tregs), B cells, and dendritic cells. In addition, we assessed the functional activity and antigenic responsiveness by analysis of third-party antigen-specific T cells after their stimulation by recall (tetanus diphtheria vaccine) antigen. In dialysis patients, we observed an expansion of CD25highCD127− Tregs after propionic acid intake. In contrast, the same supplementation did not result in any expansion of Tregs in transplant patients under immunosuppressive therapy. We also did not observe any changes in the frequencies of the main immune cell subsets except for CD4+/CD8+ distribution with an increase of CD4+ T cells and decrease of CD8+ T cells in the transplant population. Our data suggest that dietary supplements containing propionate might have a beneficial effect decreasing systemic inflammation in dialysis patients through Treg expansion. However, this effect was not observed in transplant patients, which could be explained by counteracting effect of immunosuppressive drugs preventing Treg expansion.